2018
DOI: 10.1016/j.psychres.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mindfulness meditation training on biological acute stress responses in generalized anxiety disorder

Abstract: Mindfulness-Based interventions have increased in popularity in psychiatry, but the impact of these treatments on disorder-relevant biomarkers would greatly enhance efficacy and mechanistic evidence. If Generalized Anxiety Disorder (GAD) is successfully treated, relevant biomarkers should change, supporting the impact of treatment and suggesting improved resilience to stress. Seventy adults with GAD were randomized to receive either Mindfulness-Based Stress Reduction (MBSR) or an attention control class; befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
3
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 38 publications
5
119
3
12
Order By: Relevance
“…Other randomised trials of community samples also failed to find effects on CRP 35,59 and cell counts 60 , although mindfulness meditation significantly influenced TNF-α levels in healthy individuals when individual studies were combined in a meta-analysis. Trials on clinically anxious or depressed populations found significant effects on TNF-α with samples of 60-70 participants 61,62 ; however a recent actively controlled trial with HIV patients failed to find any effects 63,27 .…”
Section: Outcome (Unit)mentioning
confidence: 97%
“…Other randomised trials of community samples also failed to find effects on CRP 35,59 and cell counts 60 , although mindfulness meditation significantly influenced TNF-α levels in healthy individuals when individual studies were combined in a meta-analysis. Trials on clinically anxious or depressed populations found significant effects on TNF-α with samples of 60-70 participants 61,62 ; however a recent actively controlled trial with HIV patients failed to find any effects 63,27 .…”
Section: Outcome (Unit)mentioning
confidence: 97%
“…Kabat-Zinn (1990) [56] defined mindfulness as "paying attention on purpose, in the present moment, and non-judgmentally, to the unfolding of experience moment to moment" (p. 23). Scientific evidence from analyses and meta-analyses has shown the results on the level of benefits of Mindfulness-based interventions (MBI), inter alia, over physical pain [57], depression [58], anxiety [59], stress and well-being [60], sleep [61], and inflammatory response [59]. In addition, approaches such as mindfulness training for introspection in the selfish-selfless spectrum are entering the mainstream of clinical care for managing pain, depression, and stress [62].…”
Section: Introductionmentioning
confidence: 99%
“…This study was novel in that it involved a multimodal mindfulness program that exposed students to an array of different activities that could facilitate stress management, but incorporated differing media that could appeal to students with varying attentional capacities, sensorimotor needs, and selfregulation skills. For example, while traditional sitting meditations have been well studied for their stress management properties (Davis et al, 2019;Hoge et al, 2018), the author's experience as educators and practitioners led to our surmise that some students would benefit more from movement based mindfulness activities, while others would prefer the incorporation of sound, visualization, and tactile experiences in combinations unique to each participant. It was an aim of this study to allow students to have autonomy in the ability to tailor the mindfulness activities to their own specific needs and preferences.…”
Section: (Participant 13)mentioning
confidence: 99%
“…Mindfulness meditation practices teach people to regulate perceived states of stress through mental training designed to facilitate attention to the present moment, relaxation, and the halting of dysfunctional thoughts (Lindsay & Creswell, 2017). Mindfulness meditation has been particularly effective at assuaging the cognitive ruminations accompanying anxiety and depression (Hoge et al, 2018;Khusid & Vythilingam, 2016). A growing body of literature has demonstrated the positive effects of mindfulness practices to reduce stress in a range of populations, including college students (Bamber & Schneider, 2016; Barbosa et al, 2013;Galante et al, 2018;Ramler et al, 2016).…”
mentioning
confidence: 99%